Sintesis Biodiesel dari Minyak Jelantah dengan Katalis K2CO3/y-Al2O3 - Handayani, Fitriyani Yetti; Cahyono, Rochim Bakti; Budiman, Arief (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Biodiesel is an environmentally friendly alternative fuels. The price of biodiesel is still relatively expensive due to the high price of raw materials. Thus, cheaper raw materials such as used cooking oils can be used. Used cooking oils can be used to produce biodiesel by transesterification reaction using alcohol and catalyst. The effect of temperature on the conversion was studied in this research. The research was carried out in batch at various temperatures of 45, 55 and 65 oC by reacting used cooking oil and bioethanol with catalyst K2CO3/γ-Al2O3. The ratio of used cooking oil and bioethanol is 1:9 and the concentration of catalyst is 3%. The reaction was run for 5, 10, 15, 30, 60, and 120 minutes, then the biodiesel was separated from the catalyst and glycerol. Furthermore, the biodiesel samples were analyzed by GC-MS to determine the alkyl ester content. The result showed that the highest conversion was 86.39% at 65oC. The biodiesel product complies with SNI 7182:2015, with a density of 871.7 kg/m3, kinematic viscosity of 4.82 mm2/s, flash point of 176oC, cloud point of 9oC, copper plate corrosion number 1, acid number 0.39 mg-KOH/g, total glycerol 0.16%, and ester content 98.3%.